Pelatihan Pengelolaan Sampah Organik di Pondok Pesantren Roudlotus Saidiyyah Semarang - Atmanti, Hastarini Dwi; Rejekiningsih, Tri Wahyu; Sasana, Hadi; Muttaqin, Aris Anwaril; Majid, Rifaldi (Pakis Journal Institute, 2026)
This community service project aims to teach people how to turn organic waste into compost. The simplest technique to use, composting can enhance the quality of the environment. The Roudlotus Saidiyyah Islamic Boarding School in Semarang was the site of the community service project. The Islamic boarding school's students had not yet sorted their waste, therefore this exercise was done. Kitchen waste accounted for the majority of the waste generated. Typically, kitchen waste is burned or dumped in the Jatibarang Landfill after being placed in the trash. CBPR, or community-based participatory research, was the approach adopted. In addition to offering counseling, this approach motivates students to actively engage in the service project. The activity's outcomes demonstrated an improvement in the students' comprehension of the 3R idea (Reduce, Reuse, Recycle) and their ability to compost.